Comparative cytogenetics in the genus Trifolium section Trifolium (clover) : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Plant Biology at Massey University - Bucknell, Tatyana Thelma (Massey University, 1999)
Five species in genus Trifolium section Trifolium were investigated cytologically. The species investigated were T. pratense, T. hirtum, T. incarnatum, T. alexandrinum and T. striatum. A new modified air-dried technique was used to prepare the chromosomes in order to overcome difficulties related to small chromosome size and also to produce metaphases suitable for fluorescence in situ hybridisation. Chromosome numbers were confirmed for all species. T. hirtum was morphometrically analysed using the confocal microscope and Silicon Graphics image analysis software, C-banded, Q-banded and subjected to fluorescence in situ hybridisation (FISH). The FISH revealed a unique distribution pattern for 18s and 5s rDNA with the 5s and 18s signals present on the satellited chromosome pair only. For 5s rDNA, hybridisation sites were observed in three areas of the satellited chromosome, two of those sites were on either side of the 18s signal. Idiograms showing chromosome lengths and the position of C-bands were also produced. T. pratense was Q-banded and its chromosome number confirmed as 2n=2x=14. The chromosome number of T. incarnatum was confirmed as 2n=2x=14 rather than 2n=2x=16 as reported in some literature; the species was also C- banded. The chromosome number of T. alexandrinum was confirmed as 2n=2x=16. The chromosome number of T. striatum was confirmed as 2n=2x=14. This is the first time any species in the genus Trifolium section Trifolium have been successfully C-banded, Q-banded, and subjected to fluorescence in situ hybridisation. The information gained will go some way towards illuminating the evolutionary relationships between species in the section Trifolium and also in the genus Trifolium, whilst also giving support to breeding programs in place and those planned for the future.
Keywords: Clover; Genetic aspects